The synergistic effect of probiotic and phytobiotic for improving growth performance and biological indices in broiler chickens - Gholami-Ahangaran, Majid; Dehkordi, M. Karimi; Ostadpoor, M; Dastgerdi, A. Ahmadi; Mahdi, O. A.; Jawad, M. A.; Mustafa, Y. F. (Journal of the Hellenic Veterinary Medical Society, 2022)
Application of phytobiotic, probiotic in poultry production can positive effect on performance, produce healthy protein sources for humans. In this study, the effects of one commercial probiotic, phytobiotic was evaluated on chicken performance. Totally, 300 chicks were divided into 4 groups that fed the basal diet, diet containing probiotic (Protexin), phytobiotic (AE), probiotic (Protexin) plus phytobiotic (AE) in all over the growing period. The growth indices were measured weekly, analyzed in 21, 42 days of age. At 42 days of age, blood samples were collected from all chickens. The concentration of liver enzymes, lipid profiles, antioxidant status were measured in blood samples. Results showed that the weight gain was significantly higher, FCR significantly lower in chickens received probiotic, or probiotic plus phytobiotic in comparison with chickens received phytobiotic, control chickens (p<0.05). Furthermore, addition of phytobiotic plus probiotic can significantly increase the activity of blood GPx, TAS with respect to chickens that received probiotic, phytobiotic, alone. The TG, CHL, LDL was lower, HDL was higher in chickens received phytobiotic or probiotic plus phytobiotic with comparison of chickens fed probiotic, control chickens (p <0.05). The level of AST, ALT, ALP show a significant decrease in chickens fed probiotic plus phytobiotic. In conclusion, continuous utilization of probiotic (Protexin) along with phytobiotic (Artichoke extract) in broiler diets can induce synergist effect on growth improvement, antioxidant capacity increasing, serum lipid reducing, liver function improvement in broiler chickens.